2022
DOI: 10.3389/fonc.2022.894485
|View full text |Cite
|
Sign up to set email alerts
|

HPGDS is a novel prognostic marker associated with lipid metabolism and aggressiveness in lung adenocarcinoma

Abstract: BackgroundLung adenocarcinoma (LUAD) is the most common respiratory globallywith a poor prognosis. Lipid metabolism is extremely important for the occurrence and development of cancer. However, the role of genes involved in lipid metabolism in LUAD development is unclear. We aimed to identify the abnormal lipid metabolism pathway of LUAD, construct a novel prognostic model of LUAD, and discover novel biomarkers involved in lipid metabolism in LUAD.MethodsBased on differentially expressed genes involved in lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…It has been shown that in mice, deletion of the gene encoding HPGDS affects pancreatic cancer development. 47 Our study is consistent with existing studies that modulation of ACOXL, EPHX2, and HPGDS has a more pronounced effect on the developmental process of endometrial cancer, and its mechanism of action needs to be further explored.…”
Section: Discussionsupporting
confidence: 92%
“…It has been shown that in mice, deletion of the gene encoding HPGDS affects pancreatic cancer development. 47 Our study is consistent with existing studies that modulation of ACOXL, EPHX2, and HPGDS has a more pronounced effect on the developmental process of endometrial cancer, and its mechanism of action needs to be further explored.…”
Section: Discussionsupporting
confidence: 92%
“…These pathways reveal a coping mechanism involving decrease in expression of proteins that are either not survival-critical under metabolic stress induced by ischemia (such as proteins involved in drug metabolism like UGT2B17 or UGT1A8) or those that are energy intensive for the cell (ribosome biogenesis). Ischemia very interestingly appears to slowly breach through this coping mechanism by causing a decrease in tumour survival-critical proteins such as NUDT1, ELOVL, HPGDS or DZIP3 [8, 9, 10, 11].…”
Section: Resultsmentioning
confidence: 99%
“…The hematopoietic prostaglandin D synthase ( HPGDS ) is a σ-like glutathione transferase that participates in the arachidonic acid metabolic pathway and catalyzes the production of prostaglandin D2, which is an important mediator of inflammation and malignant tumor growth. According to Shao et al 34 mutations of HPGDS promote lung cancer cell migration by upregulating the expression of ACSL1 and ACC, important enzymes involved in lipid metabolism. In type 2 diabetic mice, HPGDS was significantly downregulated in wounds, and its deficiency delayed normal wound healing.…”
Section: Discussionmentioning
confidence: 99%